Levetiracetam Differentially Alters CD95 Expression of Neuronal Cells and the Mitochondrial Membrane Potential of Immune and Neuronal Cells in vitro - Rogers, Susannah K.; Shapiro, Lee A.; Tobin, Richard P.; Tow, Benjamin; Zuzek, Aleksej; Mukherjee, Sanjib; Newell-Rogers, M. Karen (Frontiers in Neurology, 2014)
Epilepsy is a neurological seizure disorder that affects over 100 million people worldwide. Levetiracetam, either alone, as monotherapy, or as adjunctive treatment, is widely used to control certain types of seizures. Despite its increasing popularity as a relatively safe and effective anti-convulsive treatment option, its mechanism(s) of action are poorly understood. Studies have suggested neuronal, glial, and immune mechanisms of action. Understanding the precise mechanisms of action of Levetiracetam would be extremely beneficial in helping to understand the processes involved in seizure generation and epilepsy. Moreover, a full understanding of these mechanisms would help to create more efficacious treatments while minimizing side effects. The current study examined the effects of Levetiracetam on the mitochondrial membrane potential of neuronal and non-neuronal cells, in vitro, in order to determine if Levetiracetam influences metabolic processes in these cell types. In addition, this study sought to address possible immune-mediated mechanisms by determining if Levetiracetam alters the expression of immune receptor-ligand pairs. The results show that Levetiracetam induces expression of CD95 and CD178 on NGF-treated C17.2 neuronal cells. The results also show that Levetiracetam increases mitochondrial membrane potential on C17.2 neuronal cells in the presence of nerve growth factor. In contrast, Levetiracetam decreases the mitochondrial membrane potential of splenocytes and this effect was dependent on intact invariant chain, thus implicating immune cell interactions. These results suggest that both neuronal and non-neuronal anti-epileptic activities of Levetiracetam involve control over energy metabolism, more specifically, mΔΨ. Future studies are needed to further investigate this potential mechanism of action.